Brain structure and clinical profile point to neurodevelopmental factors involved in pedophilic disorder. (22nd January 2021) - Abé, Christoph; Adebahr, Roberth; Liberg, Benny; Mannfolk, Christian; Lebedev, Alexander; Eriksson, Jonna; Långström, Niklas; Rahm, Christoffer
Abstract: Objective: Pedophilic disorder (PD) is characterized bypersistent, intense sexual attraction to prepubertal children that the individual has acted on, or causes marked distress or interpersonal difficulty. Although prior research suggests that PD has neurodevelopmental underpinnings, the evidence remains sparse. To aid the understanding of etiology and treatment development, we quantified neurobiological and clinical correlates of PD. Method: We compared 55 self‐referred, help‐seeking, non‐forensic male patients with DSM‐5 PD with 57 age‐matched, healthy male controls (HC) on clinical, neuropsychological, and structural brain imaging measures (cortical thickness and surface area, subcortical and white matter volumes). Structural brain measures were related to markers for aberrant neurodevelopment including IQ, and the 2nd to 4th digit ratio (2D:4D). Results: PD was associated with psychiatric disorder comorbidity and ADHD and autism spectrum disorder symptoms. PD patients had lower total IQ than HC. PD individuals exhibited cortical surface area abnormalities in regions belonging to the brain's default mode network and showed abnormal volume of white matter underlying those regions. PD subjects had smaller hippocampi and nuclei accumbens than HC. Findings were not related to history of child‐related sexual offending. IQ correlated negatively with global expression of PD‐related brain features and 2D:4D correlated with surface area in PD. Conclusions: In the largest single‐center study to date, we delineate psychiatric comorbidity, neurobiological and cognitive correlates of PD. Our morphometric findings, their associations with markers of aberrant neurodevelopment, and psychiatric comorbidities suggest that neurodevelopmental mechanisms are involved in PD. The findings may need consideration in future development of clinical management of PD patients.